Procedimento para validação intralaboratorial de métodos de ensaio: delineamento e aplicabilidade em análises de alimentos - Scheilla Vitorino Carvalho de Souza Ferreira (2007)
A detailed procedure for single-laboratory validation of quantitative and qualitative methods was developed to be applied to food analysis. The procedure was based on theoretical background, considering the efficiency, practicability and easiness of the experimental design and the statistical tools for analysis of the data. The direct validation was adopted, using standard and reference materials. Linearity, matrix effects, selectivity, trueness, precision under repeatability and within-reproducibility conditions, limit of detection, limit of quantification, decision limit and detection capability were the parameters studied for quantitative methods, while selectivity and detection limit were evaluated for qualitative methods. The applicability of the proposed procedure was demonstrated for three quantitative methods (semicarbazide in baby food by high performance liquid chromatography tandem mass spectrometry, arsenic in bovine liver by hydride generation atomic absorption spectrometry and avermectins in bovine milk by high performance liquid chromatography with fluorescence detection) and one qualitative method (animal meals in ruminant feeds by microscopy). All the validated method showed fitness for the respective purposes.